Structure-Activity Relationship of Pyrrolidine Pentamine Derivatives as Inhibitors of the Aminoglycoside 6'-N-Acetyltransferase Type Ib - Jan Sklenicka; Tung Tran; Maria S. Ramirez; Haley M. Donow; Angel J. Magaña; Travis LaVoi; Yasir Mamun; Verónica Jimenez; Prem Chapagain; Radleigh Santos; Clemencia Pinilla; Marc A. Giulianotti; et al. (MDPI AG, 2024)
Resistance to amikacin and other major aminoglycosides is commonly due to enzymatic acetylation by the aminoglycoside 6'-N-acetyltransferase type I enzyme, of which type Ib [AAC(6')-Ib] is the most widespread among Gram-negative pathogens. Finding enzymatic inhibitors could be an effective way to overcome resistance and extend the useful life of amikacin. Small molecules possess multiple properties that make them attractive for drug development. Mixture-based combinatorial libraries and positional scanning strategy have led to the identification of a chemical scaffold, pyrrolidine pentamine, that, when substituted with the appropriate functionalities at five locations (R1-R5), inhibits AAC(6')-Ib-mediated inactivation of amikacin. Structure-activity relationship studies have shown that while truncations to the molecule result in loss of inhibitory activity, modifications of functionalities and stereochemistry have different effects on the inhibitory properties. In this study, we show that alterations at position R1 of the two most active compounds, 2700.001 and 2700.003, reduced inhibition levels, demonstrating the essential nature not only of the presence of an S-phenyl moiety at this location but also the distance to the scaffold. On the other hand, modifications on the R3, R4, and R5 positions had varied effects, demonstrating the potential for optimization. A correlation analysis between molecular docking values (ΔG) and the dose required for two-fold potentiation of the compounds described in this and the previous studies showed a significant correlation between ΔG values and inhibitory activity.